Exploring the long-run and short-run Relationship between macroeconomic variables and stock prices during the restructuring period: does it matter in Turkish market - Abu Alrub, Ahmad; Tursoy, Turgut; Rjoub, Husam (IBIMA, 2016)
This paper empirically investigated the dynamic relationship between Turkish stock market and macroeconomic variables, for the period span from January 2002 to December 2013. Specifically, we examined the effect of monetary policy changes during the tested period. Dummy variables were added to the model in order to overcome the effect of inflation rate targeting and exchange rate regime change in Turkey. Using VAR model, the result revealed that long-run relationship between share price index and the tested macroeconomic variables index of industrial production (IIP) Short-term interest rate (SINT), money supply (M2), and exchange rate (EXC), was maintained. Moreover, the findings from error correction term coefficient indicated that Turkish stock market adjusted its previous disequilibrium (due to positive or negative shocks) in one period at an adjustment speed of 4.449 percent monthly.
Keywords: Turkish stock price; macroeconomic variables; Error Correction Term (ECT).